2019
DOI: 10.1002/nag.3035
|View full text |Cite
|
Sign up to set email alerts
|

On the implicit immersed boundary method in coupled discrete element and lattice Boltzmann method

Abstract: The coupled discrete element method and lattice Boltzmann method (DEMLBM) has increasingly drawn attention of researchers in geomechanics due to its mesoscopic nature since 2000. Immersed boundary method (IBM) and immersed moving boundary (IMB) are two popular schemes for coupling fluid particle in DEMLBM. This work aims at coupling DEM and LBM using the latest IBM algorithm and investigating its accuracy, computational efficiency, and applicability. Two benchmark tests, interstitial fluid flow in an ideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Practically, a fluid flow with Ma ≤ 0.1 is assumed to be incompressible [59]. The computational Mach number in LBM models can be calculated as [60,61]:…”
Section: Lbmmentioning
confidence: 99%
“…Practically, a fluid flow with Ma ≤ 0.1 is assumed to be incompressible [59]. The computational Mach number in LBM models can be calculated as [60,61]:…”
Section: Lbmmentioning
confidence: 99%
“…However, hydrodynamic forces were seldom given in the literature. Our recent work 27 reported that some IBM schemes are capable of obtaining smooth profiles of particle position and velocity but unexpected oscillation of computed hydrodynamic forces can be found.…”
Section: Numerical Examples and Validationsmentioning
confidence: 99%
“…Instead of a fixed iteration number in the fixed multidirect forcing IBM, a flexible subiteration for the velocity correction is terminated when the convergence limit is satisfied. However, oscillation of hydrodynamic forces can be found in this flexible implicit IBM, especially in flows with large Reynolds number 27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al 13 applied FVM (OpenFOAM) for investigating both the kinetics of fines' removal and the micromechanisms of suffusioninduced deformation of soils. Intensive research works have also been carried out by applying LBM in coupling with DEM [14][15][16][17][18] To model a seepage-induced fine particle migration through the skeleton formed of coarse particles, Cheng et al 19 proposed a semi-resolved CFD-DEM model, wherein a resolved fictitious domain method was used to resolve the fluid flow around coarse particles and an unresolved method based on a locally averaging theory was adopted to describe interactions between fine particles and fluid flow. To study the complicated impacts of debris flow on flexible barriers, Li and Jidong 20 proposed a discrete-based approach to couple CFD with DEM, wherein they solved the continuity equation and the locally averaged Navier-Stokes equation in a discretized fluid domain.…”
Section: Introductionmentioning
confidence: 99%